Effect of nongenetic factors on semen production charecteristics of Murrah buffalo bulls at organized semen station - Shivahre, Pushp Raj; Gupta, A.K.; Panmei, A.; Chakravarty, A.K.; Bhakat, M.; Dash, S.K.; Sahoo, S.K.; Kumar, V.; Singh, M. (Buffalo Bulletin, 2017)
A study was conducted on Murrah buffalo male calves born during 1997 to 2012, reserved for breeding at Indian Council of Agricultural Research, National Dairy Research Institute, Karnal, Haryana, India to assess the influence of season and period of birth on semen production characteristics of buffalo bulls. Chi-square analysis revealed that neither season nor period had significant effect on these parameters. The result depicted that 36.47% males donated semen and 28.68% males produced freezable quality semen out of reserved males. Overall least squares means of age at first successful semen collection (AFSC), age at first successful freezing (AFSF), age at last successful freezing (ALSF), age at last successful semen collection (ALSC), semen production period (SPP), frozen semen production period (FSPP) and age at disposal (AD) were 1073.5±28.41, 1196.05±28.18, 1600.26±143.18, 1570.33±101.55, 644.28±112.05, 712.33±159.08 and 1668.25±128.53 days, respectively. Effect of season and period of birth was not found significant for all the traits except for ALSC which showed declining trend over the periods. Significant effect (P < 0.05) of age group showed that the bulls donating semen for the first time at younger age also produced semen of freezable quality at a younger age and remained in the herd producing semen for a longer duration. The age at first semen donation in Murrah males can be reduced by introducing the young male calves to training at an early age, which could increase the doses of semen obtained from each male.